Big Five Personality Factors Among Men With a Sexual Interest in Children. Issue 2 (3rd April 2019) - Jahnke, Sara; Schmitt, Sabine; Geradt, Max; Hoyer, Jürgen
Abstract: Men with a sexual interest in children or adolescents have been described as less extraverted, conscientious, and emotionally stable than controls. Yet, such studies have mostly been conducted in forensic institutions. To test whether such findings generalize to community samples, we assessed personality profiles of 123 German-speaking men with and 89 men without pedohebephilia online, using the Big Five Inventory-25. Our results indicate that men with pedophilia or hebephilia are less emotionally stable and extraverted but more conscientious than controls. We discuss study limitations and potential causes for differences in personality among community samples of men with and without pedohebephilia.